2015
DOI: 10.1074/jbc.m115.677658
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-induced Unlocking of the Inner Gate Determines the Catalytic Efficiency of a Neurotransmitter:Sodium Symporter

Abstract: Background:The mechanism coupling substrate binding to transport in neurotransmitter: sodium symporters (NSSs) is poorly understood. Significance: The data add to our mechanistic understanding of Na ϩ -coupled transport across lipid bilayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 58 publications
(64 reference statements)
6
48
2
Order By: Relevance
“…Thus donor and acceptor were in closer proximity in the presence of Na + . This is consistent with the results from previous studies [1012, 15], which applied single molecule FRET to detergent solubilized LeuT. In the micelle environment, the distances were 6.26 ± 0.21 nm and 5.16 ± 0.22 nm in the absence and presence of 200 mM Na + , respectively.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus donor and acceptor were in closer proximity in the presence of Na + . This is consistent with the results from previous studies [1012, 15], which applied single molecule FRET to detergent solubilized LeuT. In the micelle environment, the distances were 6.26 ± 0.21 nm and 5.16 ± 0.22 nm in the absence and presence of 200 mM Na + , respectively.…”
Section: Resultssupporting
confidence: 92%
“…Substrate and two sodium ions bind to the substrate binding site (S1) located in the center of the membrane [3]. The structural dynamics of LeuT have been directly measured by fluorescence resonance energy transfer microscopy (FRET) [1013], electron paramagnetic resonance (EPR) [1417], and investigated by molecular dynamics (MD) simulations [12, 1737]. These studies revealed that substrate transport by LeuT involves multiple conformations and that the structure of LeuT is highly dynamic.…”
Section: Introductionmentioning
confidence: 99%
“…For LeuT WT the specific leucine peak was unaffected by lowering the free leucine concentration (Figure 2—figure supplement 1). The F253A mutant has previously been shown to impair binding to the S1 site (Billesbølle et al, 2015; Wang et al, 2012b). Thus, F253A serves as a S1 disturbing mutant at low substrate concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of LeuT WT from Aquifex aeolicus was performed according to the protocol described previously (Billesbølle et al, 2015). LeuT WT was expressed in E. coli C41(DE3) transformed with pET16b encoding C-terminally 8xHis-tagged transporter (expression plasmid was kindly provided by Dr E. Gouaux, Vollum Institute, Portland, Oregon, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Expression and Purification of LeuT-Expression and purification of LeuT were performed as previously described (66). In short, E. coli strain C41 containing His-tagged LeuT in pET16b expression vector was cultivated in lysogeny broth with 75 g ml Ϫ1 ampicillin at 37°C shaking at 180 r.p.m.…”
Section: Experimental Methodsmentioning
confidence: 99%